Governing violence in the pastoralist space: Karrayu and state notions of cattle raiding in the Ethiopian Awash Valley - Mulugeta, Alemmaya; Hagmann, Tobias (Afrika Focus, 2008)
Based on recent fieldwork this article examines how cattle raids involving Karrayu pastoralists are governed by the local administration and customary authorities in Ethiopia’s Upper and Middle Awash Valley. It argues that the regulation of violent conflicts in areas marked by weak state presence and legitimacy must be understood as a function of multiple social orders, actors and norms. The authors draw attention to the evolving rationales of inter-ethnic cattle raids, highlight the incomplete nature of state expansion into the Karrayu pastoralist space, and scrutinize the ambiguities of government and community peacemaking. Key words: cattle raiding, pastoralism, conflict resolution, governance, Karrayu, Ethiopia